An Integrated Approach to Control Fusarium Wilt of Dalbergia sissoo - Singh, Yogendra; Verma, R. K., Jamaluddin (Indian Forester, 2002)
A study was carried out in root trainers to test the efficacy of different biofertilizers and biocontrol agents including Arbuscular Mycorrhizal fungi (AM), Rhizobium (Rh),four species of Trichoderma namely T. atroviride (Ta),T.sp.1,T.sp.2,T. polysporum (Tp) and one species of Aspergillus (As) against Fusarium wilt (seed rot and damping-off) of sissoo. Biofertilizers and biocontrol agents in various treatment combinations effectively controlled both seed rot and damping-off caused by Fusarium solani. Rhizobium alone with Aspergillus sp. Treatment was found the best to check the disease development while AM fungi, Rhizobium and T. polysporum in combination was the best among all treatments in checking the disease as well as promoting the growth.